CITIZEN REFLECTIONS BASED ON THE APPROACH TO CHILD SUPPORT IN "VALE TUDO" (2025) - Claudino, Alessandra Helen Alves; Claudino, Gabriela Caroline Alves (Seven Editora, 2026)
The social merchandising contained in the May 13, 2025 episode of the telenovela "Vale Tudo," which addressed the request for alimony by the character Lucimar (Ingrid Gaigher), proved to be a strong motivator for women in similar situations to claim a right widely specified in the country, but with little publicized access to it. In this sense, this study aims to evaluate the framing of the episode in question based on its repercussions in national and Minas Gerais media, with the objective of drawing a parallel on how a telenovela can impact society. Furthermore, secondarily, it sought to relate the cited episode to the concept of Digital Governance, in order to make evident that the digitization of state services, accompanied by rights.